Do Consumers Benefit from Supply Chain Intermediaries? Evidence from a Policy Experiment in the Edible Oils Market in Bangladesh - Emran, M. Shahe (World Bank E-Library Archive, 2016)
Commodity traders are often the focus of popular resentment. Food price hikes in 2007-2008 resulted in protests and food riots, and spurred governments to regulate traders. In March 2011, Government of Bangladesh banned delivery order traders in the edible oils market, citing cartelization, and replaced them with a dealer's network appointed by upstream refiners. The reform provides a natural experiment to test alternative models of marketing intermediaries. This paper develops three models and derives testable predictions about the effects of the reform on the intercept of the margin equation and pass-through of international price. Using wheat as a comparison commodity, a difference-of-difference analysis of high frequency price data shows that the reform led to (i) an increase in domestic prices and marketing margins, and (ii) a weakening of the pass-through of imported crude prices. The evidence is inconsistent with the standard double-marginalization-of-rents model wherein intermediaries exercise market power while providing no value-added services, or with a model where delivery order traders provide credit to wholesalers at below-market interest rates. The evidence supports a model where delivery order traders relax binding credit constraints faced by the wholesale traders